Mathematical modelling of river pollution by determining the level of dissolved oxygen and pollutant concentration - Mahadi, Nurra (2013)
A mathematical model of a coupled advection-diffusion equation of river pollution problem is investigated. The concentration of pollutants and dissolved oxygen were obtained from the model with and without dispersion coefficient for steady and unsteady states. The unsteady models were solved analytically using the method of Laplace transform for linear case and numerically by finite difference method for nonlinear case. The calculations also involved the absence and presence of half saturated oxygen with Michaelis-Menten term. A parameter analysis was carried out in order to observe the effects of each parameter involved in this model with respect to pollutant and dissolved oxygen concentration. The values of certain parameters such as velocity, cross section area, dispersion of pollutant and dissolved oxygen were obtained from the observational data in other relevant studies. The research methodology which is being implemented in this work was generic and can be used with little modification for other rivers.The mathematical model and its validated solution for Skudai River act as a decision support on the restriction and regulation to be imposed for monitoring the river pollution.